THE STATE OF THE GLOBAL MARKET OF PROJECT FINANCING AND THE PROBLEMS OF ITS DEVELOPMENT IN UKRAINE - Tetiana Mayorova; Iryna Petrenko; Iaroslav Shevchuk (Izdevnieciba "Baltija Publishing", 2019)
The article contains current analytical review of global project financing market. Some issues on economic essence of project financing were covered. It was determined that project financing is a modern financial tool with a strong potential in providing the economy with financial resources for its development. The authors researched dynamics of the global project finance market, identified its main trends and causes of changes. It was found that the global market of project financing is sufficiently volatile with some positive trends during last years. Besides, regional peculiarities of development of the project financing market were determined, the projects which are of the greatest interest to its participants were identified. It helped to make a conclusion that the development of the world project financing market highly depends on the successfulness and scale of the projects that are active in a corresponding state. The authors also found that the most priority economic sectors include power, oil and gas, transportation, leisure and property, mining. Based on the collected data, authors made their forecasts about the development of the global project financing market in 2019. They also identified the factors that impede the development of the project financing market in Ukraine. Proposals for intensification of project financing were made, in particular by developing relevant regulatory documents and establishing a national development bank.